Predicting the power of entrepreneurial orientation in improving the level of product ‎‎innovation. Business education as a mediator - Massoudi, Aram H. (Journal of Management and Business Education, 2025)
Innovative firms may react to the swift shift in the business landscape by developing new ‎competencies that allow them to attain an improved outcome. Earlier studies have stressed that ‎entrepreneurial orientation is an essential component for business success. Hence, this article will ‎determine the immediate influence of entrepreneurial orientations on product ‎innovation in the Syrian ‎pharmaceutical industry with a business education as a mediator. A primary quantitative research strategy backed ‎by qualitative input was used to ‎obtain empirical data from 264 senior executives, and innovation ‎experts and staff representing 40 pharmaceutical ‎companies in the Syrian pharmaceutical industry. The ‎finding showed that the application of entrepreneurial orientation dimensions has a significant and positive ‎influence on product innovation in the Syrian pharmaceutical ‎companies. Also, business education mediates the relation between entrepreneurial orientation and product ‎‎innovation. ‎ The article likely explores how entrepreneurial orientation influences product innovation, with business education acting as a mediator. This study is novel in examining how education strengthens the link between an entrepreneurial mindset and innovation outcomes. This highlights the potential of business education to enhance innovation-driven entrepreneurship.